Comparative Analysis of the Effectiveness of the Polish and Ukrainian Basic Training Programs for Physical Education of Primary School Students - Оleksandr Mozоlev; Maryna Khmara (Pedagogical Discourse, 2019)
The article theoretically analyzes the content of the Polish and Ukrainian basic programs of physical culture training of pupils of the ninth year of study, common approaches and features of conducting the classes. The main differences of the Polish programme have been defined, namely: other areas of education and training activities; requirements concerning mandatory physical training of the students during extracurricular time for at least 2 hours per week; group formation to physical culture lessons according to the interests; formation of the general culture of student behavior in accordance with the rules «Fair play» (respect for surrounding people, opponents and fans); development of regional authorial programs on physical culture. The results of practical testing of the impact of basic training programs on the development of moving abilities of students have been presented. It is established that indicators of development of moving abilities have a steady tendency to improve within the period of carrying out research that testifies the efficiency of the Polish and Ukrainian basic programs of physical culture training. Significant changes are observed in the development of stamina, strength stamina, balance control, legerity, development of the ability to coordinate the overall body movements of boys and girls; explosive power of girls.A comparative analysis of the impact of Ukrainian and Polish basic training programs on the level of development of the basic physical qualities of students and self-assessment of their health have been conducted. Dynamics of improvement of indicators of development of physical abilities of students in control and experimental groups has been investigated, their differences have been characterized. It is established that the self-assessment of the physical health of students has a general tendency to improve performance and significant changes that led to the transition to the higher level in the control and experimental groups.